(untitled) (El-Wahat Journal for Research and Studies, 2020)
This Study Attempts In The Light Of The Dominant Value As A Manifestation Of Literality On One Side, And As Access To The Approach And Analysis Of Another, Distinguished Essentially By Its Massive Presence Vis-A-Vis Others. Values; The Study In Question Attempts To Approach The Poetic Rhythm As A Symbolic Language Which Consists And Includes At The Same Time Several And Various Meanings Related To The Constituents Of The Poetic Experience By Choosing In This Course The Title Of The Text As The First Threshold By Supposing Its Allusions Related To The Meaning, The Structure And The General Vision Of The Poem Mentioned Above. The Study Also Draws On His Debate On The Radical Principle Of Reception Theory Marked By The Presence Of The Reader And Its Effectiveness In Inspiring Textual Structures In Their Interaction, Far From Any Form Of Impressionism Or Documentation. Key Words - (Inspiration - Rhythm-Meaning-Construction(